2022
DOI: 10.3390/ph15121533
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Integrase Strand Transfer Inhibitors and Neurodevelopment

Abstract: Children born to mothers, with or at risk, of human immunodeficiency virus type-1 (HIV-1) infection are on the rise due to affordable access of antiretroviral therapy (ART) to pregnant women or those of childbearing age. Each year, up to 1.3 million HIV-1-infected women on ART have given birth with recorded mother-to-child HIV-1 transmission rates of less than 1%. Despite this benefit, the outcomes of children exposed to antiretroviral drugs during pregnancy, especially pre- and post- natal neurodevelopment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 182 publications
3
11
0
Order By: Relevance
“…One of the gene subsets most commonly downregulated across INSTIs were those associated with extracellular matrix interactions and cell motility, including ADAM metallopeptidases, laminins and collagens, and C3 and CXCL12 , classic pro-inflammatory genes with known roles in neural structure and development ( Figures 6A–C, E ). These observations are consistent with a recent report relating integrase inhibitors’ ability to impair matrix metalloproteinase function with the frequent–yet inconclusive–clinical reports of structural defects in the developing CNS when exposed to INSTIs in utero ( Xu et al, 2017 ; Bade et al, 2021 ; Foster et al, 2022 , 2023 ; Zizioli et al, 2023 ). The majority of the significant differentially expressed genes altered by EVG were shared with RAL ( Figure 6D ), and several of the unique RAL genes also involved morphogenesis and TGF-β signaling.…”
Section: Resultssupporting
confidence: 91%
“…One of the gene subsets most commonly downregulated across INSTIs were those associated with extracellular matrix interactions and cell motility, including ADAM metallopeptidases, laminins and collagens, and C3 and CXCL12 , classic pro-inflammatory genes with known roles in neural structure and development ( Figures 6A–C, E ). These observations are consistent with a recent report relating integrase inhibitors’ ability to impair matrix metalloproteinase function with the frequent–yet inconclusive–clinical reports of structural defects in the developing CNS when exposed to INSTIs in utero ( Xu et al, 2017 ; Bade et al, 2021 ; Foster et al, 2022 , 2023 ; Zizioli et al, 2023 ). The majority of the significant differentially expressed genes altered by EVG were shared with RAL ( Figure 6D ), and several of the unique RAL genes also involved morphogenesis and TGF-β signaling.…”
Section: Resultssupporting
confidence: 91%
“…Increased neurodegeneration, including shrinkage of cytoplasm and pyknotic nuclei in CA1 and dentate gyrus, has been reported in Wistar rats exposed to TDF/3TC and efavirenz (Akang, 2019). Multiple in vitro studies report oxidative and mitochondrial stress, neurotoxicity and astrocyte senescence in cultured neurons and astrocytes exposed to monotherapy or combined antiretroviral therapy (Ellis et al, 2007;Liner et al, 2010;Robertson et al, 2012;Akay et al, 2014;Blas-García et al, 2014;Shah et al, 2016;Cohen et al, 2017;Nooka and Ghorpade, 2017;Sanchez and Kaul, 2017;De Benedetto et al, 2020;Bertrand et al, 2021;Lanman et al, 2021;Foster et al, 2022;Rudd and Toborek, 2022). While these studies investigated the direct neurotoxic effects of ARVs, our mice were only exposed to ARVs in utero.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have explored the association between various categories of ART drugs, such as NRTIs, NNRTIs, PIs, and INSTIs, and neurotoxicity ( Blanche et al, 1999 ; Cepeda and Wilks, 2000 ; Streck et al, 2008 ; Streck et al, 2011 ; Abers et al, 2014 ; Underwood et al, 2015 ; Hoffmann and Llibre, 2019 ; Zash et al, 2019 ; Foster et al, 2022 ); however, their relationship remains to be elucidated. In this study, we investigated which classes of ART drugs are associated with the risk of neurological diseases in patients with HIV/AIDS in Taiwan and observed that low cumulative DDDs or poor adherence to ART drugs increase the risk of neurological diseases across various classes of drugs, including NRTIs, PIs, NNRTIs, INSTIs, and multi-drug tablets.…”
Section: Discussionmentioning
confidence: 99%
“…ART drugs are classified based on their distinct molecular mechanisms and pharmacological characteristics, such as nucleoside reverse-transcriptase inhibitors (NRTIs), protease inhibitors (PIs), non-nucleoside reverse-transcriptase inhibitors (NNRTIs), integrase strand transfer inhibitors (INSTIs), fusion inhibitors, and co-receptor antagonists ( Arts and Hazuda, 2012 ; Nastri et al, 2023 ). Neurotoxicity is linked to different classes of antiretroviral drugs, including NRTIs, NNRTIs, PIs, and INSTIs ( Abers et al, 2014 ; Xu et al, 2014 ; Underwood et al, 2015 ; Hoffmann and Llibre, 2019 ; Zash et al, 2019 ; Foster et al, 2022 ). Furthermore, studies have reported that NRTI administration is associated with an increased risk of neurotoxicity in both the CNS and peripheral nervous system ( Blanche et al, 1999 ; Cepeda and Wilks, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation